2016
DOI: 10.1103/physrevb.94.144407
|View full text |Cite
|
Sign up to set email alerts
|

Magnon-drag thermopower and Nernst coefficient in Fe, Co, and Ni

Abstract: Magnon-drag is shown to dominate the thermopower of elemental Fe from 2 to 80 K and of elemental Co from 150 to 600 K; it is also shown to contribute to the thermopower of elemental Ni from 50 to 500 K. Two theoretical models are presented for magnon-drag thermopower. One is a hydrodynamic theory based purely on non-relativistic, Galilean, spinpreserving electron-magnon scattering. The second is based on spin-motive forces, where the thermopower results from the electric current pumped by the dynamic magnetiza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
117
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 124 publications
(125 citation statements)
references
References 50 publications
8
117
0
Order By: Relevance
“…[29] and [30], respectively, the room-temperature magnonic contribution S to the thermopower of symmetric tunnel junctions is obtained then to be significant when compared with the free-electron one. Similar estimates have been made in the context of the measured bulk thermopower in metallic ferromagnets [8].…”
Section: Discussion and Outlooksupporting
confidence: 74%
See 2 more Smart Citations
“…[29] and [30], respectively, the room-temperature magnonic contribution S to the thermopower of symmetric tunnel junctions is obtained then to be significant when compared with the free-electron one. Similar estimates have been made in the context of the measured bulk thermopower in metallic ferromagnets [8].…”
Section: Discussion and Outlooksupporting
confidence: 74%
“…1. At low temperatures, i.e., T T C ,T F (with T C and T F being the Curie and Fermi temperature, respectively), the electric current is controlled by the voltage V applied to the 2469-9950/2017/96(9)/094429 (8) 094429-1 ©2017 American Physical Society…”
Section: A Phenomenology Of Magnetic Pumpingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Eqs. (38) and (40) the function y 1 is also stationary at H = H ⊥ , but it has a minimum only for η < 1, while an inflection point for η = 1, and a maximum otherwise. The resulting dependence on η of Eq.…”
Section: A Spin and Heat Transportmentioning
confidence: 92%
“…1 To that end, phonon drag had been shown to enhance the Nernst coefficient at low temperatures in certain material systems. 3,4 More recently, Watzman et al reported that the anomalous Nernst coefficient also benefits from magnon drag as shown in single crystal Fe where N ANE is dominated by magnon drag up to 200 K. 5 In this study, we propose using a magnetostrictive metallic metal, Galfenol (Fe 100-x Ga x ), as a pathway to increase the power factor due to its enhanced Nernst coefficient from phonon and magnon coupling, as well as its large intrinsic electrical conductivity. We demonstrate Nernst voltage generation in a coiled Galfenol wire, characterize its Nernst coefficient, and offer an experimental proof-of-concept for a novel and scalable thermoelectric generator ideal for cylindrical heaters.…”
mentioning
confidence: 93%